Fielding - Dobson, Austin, 1840-1921 (Salt Lake City, UT : Project Gutenberg, 2004)
"Fielding" by Austin Dobson is a biographical account focusing on the life and works of the English novelist and playwright Henry Fielding, written in the late 19th century. The book aims to present a thorough examination of Fielding's life, correcting past misconceptions and offering fresh insights into his personal and professional experiences. The opening of the memoir outlines Fielding's lineage and early years, detailing his birth into an ancient family and the influences that shaped his literary career. It presents a broad picture of his upbringing, education at Eton, and the early romantic escapades that hinted at his later literary pursuits. Dobson introduces various anecdotes about Fielding's family and education while alluding to his gradual emergence into the world of theater and his budding interest in playwriting, laying the groundwork for understanding Fielding's character as a dramatist and novelist. (This is an automatically generated summary.)
Release date is 2004-10-01
Produced by Tonya Allen, Charles Aldarondo, Charles Franks and the Online Distributed Proofreading Team
Keywords: Fielding, Henry, 1707-1754; Authors, English -- 18th century -- Biography